Potassium voltage-gated channel subfamily H member 1 (KCNH1) missense mutation causing epileptic encephalopathy and autistic behaviour - Prem Chand,; Sulaiman, Asna; Kirmani, Salman (Journal of the Pakistan Medical Association, 2023)
The phenotypically similar genetic diseases Zimmermann-Laband syndrome (ZLS) and Temple-Baraitser syndrome (TMBTS) cause neurodevelopmental problems. Mutations in the gene coding for potassium voltage-gated channel, primarily KCNH1, cause these symptoms. An uncommon mutation in KCNH1 (p.Arg357Trp) present on Exon 7, reported to replace arginine with tryptophan at codon 357 of the KCNH1 protein c.1069C>T, caused pharmacoresistant seizures and autistic behaviour in a 2.7-year-old boy. This mutation causes problems with protein modelling and has yet to be documented in any genetic databases around the world. This mutation was overlapped with GPHN gene, c.828+1G>A, in our patient, causing GPHN-related spectrum disorder (autosomal dominant) along with molybdenum cofactor deficiency (autosomal recessive) leading to a neuropsychiatric presentation including autistic behaviour, making diagnosis and management even more complicated. Keywords: Zimmermann-Laband syndrome, Temple-Baraitser syndrome, Autism, KCNH1 (p.Arg357Trp)